Karakteristik Façade Rumah Toko (Ruko) di Kawasan Pasar Tengah di Kota Pontianak - R. Puspito Harimurti; Erwin Rizal Hamzah; Chandra Bayu (Vokasi, 2020)
Central Market in Pontianak City is one of the trade centers that was first built in Pontianak City by people of Chinese descent. along with the growth of this region as a trade center in Pontianak City, this region suffered a setback due to the transition of the city economic growth center which is no longer fully oriented to activities on the banks of the Kapuas River. The purpose of this study is to carry out an inventory and identification of typical characteristics of Shophouse building (RUKO) in the Central Market area in Pontianak City, as well as identifying the diversity of the appearance of the Chinatown building facade in Pontianak through the study of building typology and the changing pattern of facade appearance. This study uses a rationalistic-qualitative approach with a qualitative descriptive approach to the facade typology of Ruko buildings in the Central Market area in Pontianak City. Descriptive research flow starts from the information units or objects that are observed gradually, the findings are dialogue (abstracted) to compile general themes that at the end of the abstraction process, a final finding can be found in the form of local theory (character and typology of Ruko in the Market area Central in Pontianak City). The form of analysis of this research is to use a descriptive approach. The results of this study indicate that there are three types of doors that are dominantly used, namely: (a) Doors with a Rolling Door top and folding side models, (b) Doors with Jalousie, and: (c) Wooden sliding folding doors. There are four types of windows, namely: (a) Window glass with grid pattern, (b) Glass window with Plain model, (c) Window with Nako model, (d) Window with Jalusi model. There are three types of signage (signage), namely (a) Placing markers (signage) on the walls and windows of buildings, (b) Placing signage on the arcade section, (c) model of laying signage on the arcade pole. There are four typologies of the roof, namely: (a) Flat Roof (Dak), (b) Saddle Roof, (c) Limasan Roof, (d) Limasan Roof. There are four typologies of shading, namely: (a) Shading with Arcade, (b) Shading with Canopy, (c) Shading with Extension of Roof Tritisan, (d) Shading with Dividing Wall and (e) Shading by Balcony.